Analisis Tinggi Muka Air Banjir Sebagai Upaya Penyelamatan Tebing Sungai Batang Gansal di Desa Seberida-Indragiri Hulu - Husaini, Rizki Ramadhan; Jusatria, Jusatria (Journal of Infrastructure and Civil Engineering, 2022)
Floods are generally caused by a discharge of water flowing in a river that exceeds the cross-sectional capacity of the river. In addition, the topography of a land also affects the flood water level. Seberida Village is one of the villages located on the banks of the Indragiri river which is prone to flooding. The research aims to analyze the amount of flood discharge using rainfall data with a vulnerability of 2004-2020. Rainfall data was obtained from collecting 2 rain stations, namely PCH Keritang and PCH Usul. The flood level elevation was analyzed using modeling from the HecRas software and bathymetric measurement data in the field. Based on the results of the flood discharge analysis using the Nakayasu method, a flood discharge with a return period of 2 years is 286,485 m3/second; 5 year return period of 448,902 m3/second; 10 year return period of 555.564 m3/second, 20 year return period of 611.31950 m3/second and 50 year return period of 670.774 m3/second. As for the flood water level in the Seberida river, it is at an elevation of 35.51m with an inundation area of ??4.9 Ha. From the results of this study, it is necessary to make safeguards for the Batang Gansal river bank to anticipate cliff collapse due to high flood fronts that may occur.